(untitled) (One Health & Risk Management, 2025)
Introduction. Gold nanoparticles (AuNPs) have gained increasing attention in nanomedicine due to their biocompatibility and unique physicochemical properties, which make them suitable for targeted therapies against cancer and other chronic diseases. Functionalizing AuNPs with bioactive compounds further enhances their biocompatibility and therapeutic potential. This study aimed to evaluate the effects of 10 nm citrate-stabilized AuNPs functionalized with a protein extract from Arthrospira platensis (AuNPs-APE) on biodistribution, as well as hematological and biochemical parameters, in Wistar rats. Material and methods. FTIR spectroscopy confirmed AuNPs’ functionalization. Wistar rats received oral doses of AuNPs or AuNPs-APE for 28 days, followed by a 28-day clearance period. Gold biodistribution was analyzed in organs collected at the end of the experiment. Hematological and biochemical profiles were assessed using standard methods. Results. FTIR analysis confirmed stable AuNPs-protein interactions. Both AuNPs and AuNPs-APE exhibited notable renal accumulation, suggesting extraglomerular retention. The protein extract showed mild immunomodulatory effects, reducing oxidative stress and inflammation associated with nanoparticle exposure. Conclusions. The AuNPs–APE complex shows promise as a renal-targeted nanotherapeutic system, demonstrating improved biocompatibility and reduced systemic stress compared with unmodified AuNPs. Further studies are required to elucidate the underlying mechanisms and to optimize the formulation and safety profile.